Characterizing the spatial distribution of multiple malaria diagnostic endpoints in a low-transmission setting in Lao PDR - Byrne, Isabel; Cramer, Estee; Nelli, Luca; Rerolle, Francois; Wu, Lindsey; Patterson, Catriona; Rosado, Jason; Dumont, Elin; Tetteh, Kevin K. A.; Dantzer, Emily; Hongvanthong, Bouasy; Fornace, Kimberley M.; et al. (Frontiers in Medicine, 2022)
The epidemiology of malaria changes as prevalence falls in low-transmission settings, with remaining infections becoming more difficult to detect and diagnose. At this stage active surveillance is critical to detect residual hotspots of transmission. However, diagnostic tools used in active surveillance generally only detect concurrent infections, and surveys may benefit from sensitive tools such as serological assays. Serology can be used to interrogate and characterize individuals' previous exposure to malaria over longer durations, providing information essential to the detection of remaining foci of infection. We ran blood samples collected from a 2016 population-based survey in the low-transmission setting of northern Lao PDR on a multiplexed bead assay to characterize historic and recent exposures to Plasmodium falciparum and vivax. Using geostatistical methods and remote-sensing data we assessed the environmental and spatial associations with exposure, and created predictive maps of exposure within the study sites. We additionally linked the active surveillance PCR and serology data with passively collected surveillance data from health facility records. We aimed to highlight the added information which can be gained from serology as a tool in active surveillance surveys in low-transmission settings, and to identify priority areas for national surveillance programmes where malaria risk is higher. We also discuss the issues faced when linking malaria data from multiple sources using multiple diagnostic endpoints.